Implementasi WebRTC pada Sistem Multimedia Teleconference untuk Komunikasi Pembelajaran Tunarungu - Darma Wahyu R Prameswara; Dany Primanita Kartikasari; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
The process of education and learning in public schools has limitations on communication problems for the deaf. The communication process in public schools is based on verbal language, whereas the deaf rely on sign language to communicate. Based on this problem, an auxiliary communication tool is needed to carry out learning with deaf students. The systems used in the e-learning process can support the learning process of deaf students. The main feature in this learning process is converting voice into sign language in real-time. Two-way communication requires video, audio, and chat. The system is set up using Web Realtime Communication (WebRTC) as a real-time data transfer protocol using a browser.